Strengthening Young Farmers’ Capacity in Implementing a Circular Economy through Zero-Waste for Sustainable Beef Cattle Farming in Tani Bhakti Village, Kutai Kartanegara - I Putu Gede Didik Widiarta; Cori Qamara; Dani Nur Arifin; Novemia Fatmarischa; Kirana Dara Dinanti Adiputra (Bakti Cendana, 2026)
Efficient waste management becomes a key factor in reducing negative environmental impacts while improving the operational efficiency of livestock farming. This community service activity aims to enhance young livestock farmers' understanding and skills in Tani Bhakti Village, Loa Janan Subdistrict, Kutai Kartanegara Regency, in applying zero-waste, circular-economy principles in livestock waste management. This activity involved 20 young farmers from diverse backgrounds and genders. The activity included socialization, extension services, technical training, and direct demonstrations in processing livestock waste into value-added products, such as organic fertilizer and bioenergy. The method used was Participatory Action Research (PAR), which involved farmers as active participants at every stage of the activity. Evaluation was conducted through pre-test and post-test questionnaires to measure improvements in knowledge, as well as direct observation of the application of waste management techniques. The results showed that 90% of participants successfully improved their understanding of the circular economy, and 85% applied the acquired waste management techniques. The main constraints identified were limited technical understanding and access to technology. This community service activity successfully enhanced the operational sustainability of livestock farming and reduced environmental impacts.